Skeletal light-scattering accelerates bleaching response in reef-building corals. Issue 1 (December 2016) - Swain, Timothy; DuBois, Emily; Gomes, Andrew; Stoyneva, Valentina; Radosevich, Andrew; Henss, Jillian; Wagner, Michelle; Derbas, Justin; Grooms, Hannah; Velazquez, Elizabeth; Traub, Joshua; Kennedy, Brian; et al.
Abstract Background At the forefront of ecosystems adversely affected by climate change, coral reefs are sensitive to anomalously high temperatures which disassociate (bleaching) photosynthetic symbionts (Symbiodinium ) from coral hosts and cause increasingly frequent and severe mass mortality events. Susceptibility to bleaching and mortality is variable among corals, and is determined by unknown proportions of environmental history and the synergy ofSymbiodinium - and coral-specific properties.Symbiodinium live within host tissues overlaying the coral skeleton, which increases light availability through multiple light-scattering, forming one of the most efficient biological collectors of solar radiation. Light-transport in the upper 200 μm layer of corals skeletons (measured as 'microscopic' reduced-scattering coefficient, μ ^′_S, m μ S, m ′ ), has been identified as a determinant of excess light increase during bleaching and is therefore a potential determinant of the differential rate and severity of bleaching response among coral species. Results Here we experimentally demonstrate (in ten coral species) that, under thermal stress alone or combined thermal and light stress, low- μ ^′_S, m μ S, m ′ corals bleach at higher rate and severity than high- μ ^′_S, m μ S, m ′ corals and theSymbiodinium associated with low- μ ^′_S, m μ S, m ′ corals experience twice the decrease in photochemical efficiency. We further modelled the light absorbed bySymbiodinium due to skeletal-scattering and show that the estimated skeleton-dependent light absorbed bySymbiodinium (per unit of photosynthetic pigment) and the temporal rate of increase in absorbed light during bleaching are several fold higher in low- μ ^′_S, m μ S, m ′ corals. Conclusions While symbionts associated with low- μ ^′_S, m μ S, m ′ corals receive less total light from the skeleton, they experience a higher rate of light increase once bleaching is initiated and absorbing bodies are lost; further precipitating the bleaching response. Because microscopic skeletal light-scattering is a robust predictor of light-dependent bleaching among the corals assessed here, this work establishes μ ^′_S, m μ S, m ′ as one of the key determinants of differential bleaching response.